Sex Hormone-binding Globulin, Cardiometabolic Biomarkers, and Gestational Diabetes: A Longitudinal Study and Meta-analysis - Meng-Ying Li; Shristi Rawal; Stefanie N. Hinkle; Ye-Yi Zhu; Fasil Tekola-Ayele; Michael Y. Tsai; Si-Min Liu; Cui-Lin Zhang; Yang Pan (Wolters Kluwer Health, 2020)
Abstract. Objective:. This study investigated the prospective associations of circulating levels of sex hormone-binding globulin (SHBG) levels with cardiometabolic biomarkers and risk of gestational diabetes (GDM) during pregnancy. It also examines the longitudinal trajectory of SHBG in women with and without GDM. Methods:. We conducted a nested case-control study of 107 incident GDM cases and 214 matched controls within the Eunice Kennedy Shriver National Institute of Child Health and Human Development Fetal Growth Studies-Singleton Cohort. The cohort enrolled non-obese and obese women aged 18-40 years with a singleton pregnancy between 8 and 13 weeks of gestation from 2009 to 2013. GDM was ascertained via medical records review. Blood samples were drawn four times at gestational weeks 10-14, 15-26, 23-31, and 33-39. The prospective associations between SHBG levels and cardiometabolic biomarkers were examined using the Spearman partial correlation among the controls. The longitudinal trajectories of SHBG levels were examined among the cases and the controls. Meta-analysis of prospective studies were performed to examine the association between SHBG levels and GDM risk. Results:. SHBG levels at gestational weeks 10-14 were significantly inversely associated with fasting insulin (r = −0.17, P = 0.01) and insulin resistance as measured by HOMA-IR (r = −0.17, P = 0.01) at gestational week 15-26. SHBG at gestational weeks 10-14 and 15-26 was lower in cases than controls (mean ± standard deviation: (204.0 ± 97.6) vs. (220.9 ± 102.5) nmol/L, P = 0.16 and (305.6 ± 124.3) vs. (322.7 ± 105.1) nmol/L, P = 0.14, respectively), yet the differences were not significant. In the meta-analysis, SHBG was 41.5 nmol/L (95% confidence interval: 23.9, 59.1, P < 0.01) significantly lower among women with GDM than without, and each 50 nmol/L increase in SHBG was significantly associated with an odds ratio of 0.85 (95% confidence interval: 0.76-0.95, P = 0.01) for GDM. Conclusion:. Lower SHBG levels in early pregnancy were prospectively associated with higher high insulin levels and insulin resistance in mid-pregnancy and subsequent risk of GDM, independent of adiposity. SHBG may serve as a marker for the identification of high-risk pregnancies during early pregnancy.